OPTIMALISASI STANDAR PROSES DALAM PENGEMBANGAN KOMPETENSI LULUSAN DI MI RAUDLATUL MU'ALLIMIN MADIUN - Rania Salsabila; Nur Arifah (Jurnal Riset Multidisiplin Edukasi, 2026)
MI Raudlatul Mu'allimin Madiun is one of the basic education that is in demand by the local community, because the programs in the institution can produce good output. Departing from this phenomenon, the author's initiative emerged to find out in depth about the optimization of the program so that it produces superior students. The strategy taken by the author to explore this phenomenon is by analyzing planning in the learning process and implementation/implementation of the learning process so that inhibiting factors and supporting factors can be identified in terms of supervision and assessment for students at MI Raudlatul Mu'allimin Madiun. The method used in this study is a descriptive qualitative method, meaning that researchers describe, describe and illustrate the data that has been collected so that they will obtain a general and comprehensive picture of the truth. The data collection methods used are observation, interviews, and documentation. The subjects of the study were the Principal, Deputy Curriculum, teachers/educators, and guardians of MI Raudlatul Mu'allimin Madiun. The data analysis method uses the source triangulation method. The results of the study show that the process standards in institutions use various methods, where the process/program produces students who are knowledgeable and have good morals, whose interests and talents are channeled, and who are competent educators.